2008
DOI: 10.1111/j.1600-0706.2008.17171.x
|View full text |Cite
|
Sign up to set email alerts
|

Resource availability and ecosystem size predict food‐chain length in pond ecosystems

Abstract: Food‐chain length (FCL) in ecosystems has been studied extensively, and numerous hypotheses to predict FCL, productivity, ecosystem size, and productive space have been proposed. For example, the productivity hypothesis suggests that resource availability limits FCL, whereas the productive‐space hypothesis predicts that per‐unit‐size resource availability and ecosystem size equally limit FCL. However, previous studies have only measured total productivity to test FCL and have never tested the impact of resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 36 publications
(84 reference statements)
3
58
0
4
Order By: Relevance
“…Recent empirical studies have shown that food-chain length is positively correlated with habitat size (Spencer & Warren 1996;Post et al 2000a;Takimoto et al 2008;Doi et al 2009). Our model provides two possible explanations for these observations: one is related to changes in species richness and the other to interspecific spatial segregation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent empirical studies have shown that food-chain length is positively correlated with habitat size (Spencer & Warren 1996;Post et al 2000a;Takimoto et al 2008;Doi et al 2009). Our model provides two possible explanations for these observations: one is related to changes in species richness and the other to interspecific spatial segregation.…”
Section: Discussionmentioning
confidence: 99%
“…This value can be estimated in natural ecosystems by using the stable isotope technique (Vander Zanden et al 1999;Post et al 2000a;Takimoto et al 2008;Doi et al 2009). For runs with multiple top predators and/or basal species, we used the maximum value among all combinations of top predator and basal species.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Although productivity generally increases FCL (Thompson and Townsend 2005;Hoeinghaus et al 2008;Doi 2012), the effects of the magnitude of ecosystem size could positively (Post et al 2000;Takimoto et al 2008;Doi et al 2009;McHugh et al 2010;Sabo et al 2010) or neutrally (Thompson and Townsend 2005;Warfe et al 2013) influence FCL. Furthermore, the effects of disturbance on FCL are highly variable and could be positive (Calizza et al 2012), neutral (Walters and Post 2008;Warfe et al 2013), or even negative (McHugh et al 2010;Sabo et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, available energy as resource must set some upper limit to the number of trophic levels proportionately to the space available on which the successive top trophic levels can forage (Schoener, 1989). On verifying a productivity-space hypothesis, Doi et al (2009) demonstrated longer food chain length at high C level (as productivity) and maximum ecosystem size (space). These coupling factors would have maximum affect on food chain in river or lakes rather than ocean.…”
Section: Introductionmentioning
confidence: 98%